THE EFFECT OF WORK MOTIVATION, WORK FACILITIES, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. LASKAR TEKNIK INDONESIA - Mustapa, Zainuddin (XXXX-XXXX, 2024)
This study aims to examine, analyze, and interpret the effect of Work Motivation, Work Facilities, and Job Satisfaction on the performance of employees at PT. Reads Media Indonesia. The research is descriptive-quantitative in nature. The population and sample consist of 32 employees. Data collection methods include interviews, questionnaires, and literature studies. The research data will be analyzed using statistical testing tools with SPSS 24 software. The results of the study show that: Work Motivation has a positive and significant effect on the performance of employees at PT. Laskar Teknik Indonesia. In general, Work Motivation has a strong influence on improving employee performance. Employee performance is crucial for achieving organizational goals. Work Facilities have a positive and significant effect on the performance of employees at PT. Reads Media Indonesia. Work Facilities are a crucial factor that supports employees’ activities, encouraging them to consciously use their full energy and thought processes to support the organization’s objectives. Job Satisfaction has a positive and significant effect on the performance of employees at PT. Reads Media Indonesia. The goal of Job Satisfaction is to meet the employees’ economic needs and to increase work productivity in advancing the organization, as employees are motivated to work better to achieve the set training targets.